A Bibliometric Study of Models Fostering Critical Thinking, Communication, Creativity, and Collaboration Skills - Frita Dwi Wijayanti; Sarwanto Sarwanto; Dewanto Harjunowibowo (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study aims to explore instructional models that foster 21st-century skills in secondary school physics education, focusing on critical thinking, communication, creativity, and collaboration. A bibliometric analysis was conducted on 142 publications from the past decade, utilising tools such as VOSviewer to identify dominant learning approaches, including Project-Based Learning (PjBL), guided inquiry, and STEM education. The results indicate that while STEM education significantly influences physics learning, specific research in this area remains limited. Key findings reveal the effectiveness of collaborative teaching methods, digital tools, and tailored interventions in enhancing students' practical application of these skills. This research provides valuable insights for educators and researchers seeking to cultivate essential physics education competencies, addressing the educational landscape's evolving demands.